2023
DOI: 10.1021/acs.jcim.2c01503
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel CB2 Ligands through Virtual Screening and In Vitro Evaluation

Abstract: Cannabinoid receptor type 2 (CB2) is a very promising therapeutic target for a variety of potential indications. However, despite the existence of multiple high affinity CB2 ligands, none have yet been approved as a drug. Therefore, it would be beneficial to explore new chemotypes of CB2 ligands. The recent elucidation of CB2 tertiary structure allows for rational hit identification with structure-based (SB) methods. In this study, we established a virtual screening workflow based on SB techniques augmented wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…5 & Table 3. According to Ogbodo et al, 2023, reported that 6-hydroxyluteolin had a one of better interacts with potential inhibitors targeting cdk1 in colorectal cancer 20 .…”
Section: -Hydroxyluteolinmentioning
confidence: 99%
“…5 & Table 3. According to Ogbodo et al, 2023, reported that 6-hydroxyluteolin had a one of better interacts with potential inhibitors targeting cdk1 in colorectal cancer 20 .…”
Section: -Hydroxyluteolinmentioning
confidence: 99%
“…However, the solution of the crystal structure for the CB2 receptor (61) has enabled rational drug design approaches (62,63) which have the potential to provide candidate drug molecules that could be tested in the clinic in the near future.…”
Section: Microglial Cells Have Numerous Functions That Include Phagoc...mentioning
confidence: 99%